2020
DOI: 10.1155/2020/7159340
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Differentially Expressed circRNAs Reveals a Colorectal Cancer-Related ceRNA Network

Abstract: The morbidity and mortality of colorectal cancer (CRC) remained to be very high worldwide. Recently, circRNAs had been revealed to have a crucial role in cancer prognosis and progression. Numerous researches have shown that RNA sequencing technology and in silico method were widely used to identify pathogenic mechanisms and uncover promising targets for diagnosis and therapy. In this study, these methods were analyzed to obtain differentially expressed circRNAs (DECs). We identified upregulated 316 circRNAs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…A circRNA/miRNA/mRNA network was established to underlie the mechanism of circRNA in CRC [ 31 ]. After analyzing the targets of circPTK2, our study firstly validated miR-136-5p was targeted by circPTK2.…”
Section: Discussionmentioning
confidence: 99%
“…A circRNA/miRNA/mRNA network was established to underlie the mechanism of circRNA in CRC [ 31 ]. After analyzing the targets of circPTK2, our study firstly validated miR-136-5p was targeted by circPTK2.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in uveal-melanoma tissue, JPH1 expression was downregulated compared to normal tissue [ 123 ]. An analysis by Que et al [ 124 ] revealed that JPH1 was one of 14 mRNA transcripts involved in regulating a microRNA-circRNA network of genes likely involved in the development or prevention of colorectal cancer [ 124 ]; whether JPH1 -expression was upregulated or downregulated was not reported in this analysis. A mutation in the JPH1 gene was noted in a patient with human T-lymphotropic virus type-1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis who subsequently developed adult T-cell leukemia [ 125 ].…”
Section: Discussionmentioning
confidence: 94%
“…TRPM5 encodes a voltage-sensitive monovalent cation-selective channel, which is activated by elevated Ca 2+ [ 91 , 124 ]. EA can also influence TRPM5 -activity [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the functions of circRNAs remain largely unknown, the circRNA-miRNA-mRNA axis is known to regulate the development of different types of cancers ( 25 – 27 ). Exo-circRNAs may play a similar role in CRC ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%